The Digital Double: What is Synthetic Data in Medical AI Training? - Rasit Dinc (Rasit Dinc Digital Health & AI Research, 2024)
The rapid advancement of Artificial Intelligence AI in medicine is constrained by a critical resource: data. Medical data is sensitive, siloed, and scarce, p...
Keywords: Drug Discovery; Digital Health; Diagnostics; Artificial Intelligence; Healthcare Innovation